Gas source localization and mapping with mobile robots: A review - Francis, Adam; Li, Shuai; Griffiths, Christian; Sienz, Johann (Journal of field robotics, 2022)
Within the last couple of decades, there has been increasing research into the use of mobile robots for gas sensing applications. This has led to many different branches of research, most notably on the topics of gas distribution mapping and source localization. This paper aims to provide an up to date and comprehensive overview of the research on these topics for both controlled and uncontrolled environments with ground‐based or aerial robots. To complement other review papers, a greater focus is placed on recent probabilistic algorithms developed for both single robot and multirobot applications.